Pengaruh Penyimpanan Pada Suhu Rendah (Freezer -3oC) Terhadap Kandungan Air dan Kandungan Lemak pada Ikan Lemuru (Sardinella longiceps) - Anna Handayani; Alimin Alimin; Wa Ode Rustiah (Study Program of Chemistry - Alauddin State Islamic University of Makassar, 2014)
One of the peaceful and best pickling methode to maintain freshness of product is depository at low temperature (freezer). Through depository of process industrial balance and availability of processing result of fishery will remained to be taken care of. Depository of fish raw material specially of fish flesh expected will be more be economic in course of depository at low temperature (freezer). The fat rate before is depository (0 day) that is 5,14%, while at depository 1 day until 3 day of it fat is 9,43%, 14,70%, 15,30%, and to 4 until 7 days the fat content is downhill that is 7, 15%, 5, 50%, 3,96%. The rate irrigate before is depository (0 day) that is 26, 96%. While at depository 1 day until 3 day of its water that is 27, 87%, 27, 44%, 27,20%, and depository to 4 day until 7 days water content mount that is 27,94%, 27,97%, 28,10%, 28,40%. Depository of lamuru fish flesh (sardinella longiceps) conducted by at low temperature (freezer -3oC) during 7 day can cause degradation quality of good fish flesh of fat rate and also lamuru fish flesh colour changing from squeezing colour to become to squeeze to turn pale. While its water content is depository longer progressively increase.